2018
DOI: 10.1002/asia.201801052
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electronic and Magnetic Properties of Graphene‐Embedded Transition Metal‐N4 Complexes: Insight From First‐Principles Calculations

Abstract: Motivated by the development of transition-metal-nitrogen-carbon (TM-N-C) materials for catalysts and molecular electronics, we investigated the electronic and magnetic properties of TMN -graphene materials with different central atoms (TM=Ti, V, Cr, Mn, Fe, Co, Ni and Cu) and different concentrations. The first-principles results show that a widely tunable magnetic moment in the range from 0 to 4 μ can be obtained in this kind of material by varying the central TM atom, and a regular transition of the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…In their study, doping oxidized sulfur functionalities realizes an electron withdrawal on the carbon plane which decreases the energy of the d-orbital of the Fe ion, facilitating ORR at the Fe–N 4 site, while the introduction of thiophene-like sulfur functionalities makes the carbon plane electron-rich and decreases the corresponding ORR activity. Moreover, our previous study revealed that the magnetic characteristics and thus the catalytic activity of MnN 4 –graphene can be significantly tuned by the concentration of TMN 4 moieties . All the aforementioned studies show that the catalytic activity of TM–N–C has a close relationship with its locally magnetic characteristics due to the existence of 3d electrons. …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In their study, doping oxidized sulfur functionalities realizes an electron withdrawal on the carbon plane which decreases the energy of the d-orbital of the Fe ion, facilitating ORR at the Fe–N 4 site, while the introduction of thiophene-like sulfur functionalities makes the carbon plane electron-rich and decreases the corresponding ORR activity. Moreover, our previous study revealed that the magnetic characteristics and thus the catalytic activity of MnN 4 –graphene can be significantly tuned by the concentration of TMN 4 moieties . All the aforementioned studies show that the catalytic activity of TM–N–C has a close relationship with its locally magnetic characteristics due to the existence of 3d electrons. …”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have revealed that the catalytic activity of TM–N–C mainly depends on the type of TM atoms and the morphology of the carbon material, but other factors are also found to be important to some extent. For example, Li et al have reported that FeN 3 –graphene can catalyze the conversion of dinitrogen to ammonia but FeN 4 –graphene cannot, due to that the former has a much higher spin state. They also found that the cooperative spin transition between adjacent Fe atoms can affect the spin configuration and thus the catalytic activity of the system. Mun et al reported that the ORR activity of the FeN 4 site can be tuned by controlling the electron-withdrawing/donating properties of the carbon plane by incorporating different sulfur functionalities .…”
Section: Introductionmentioning
confidence: 99%
“…Previous works ,, have revealed that the doping concentration can change the electronic and magnetic properties of catalysts, and thus the catalytic activity. Therefore, we evaluated the effect of B concentration on the catalytic performance of B/g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…As the smallest defect, TM@N 3 ‐GR (shown in Scheme 1a) is created by removing one carbon atom from GR and replacing the three adjacent carbon atoms by nitrogen atoms. To fabricate the most common TM@N 4 ‐GR‐I (shown in Scheme 1b), [1d,f,9] two carbon atoms are removed from GR and four surrounding carbon atoms are replaced by nitrogen atoms. We also designed similar defects to TM@N 4 ‐GR‐I with different substituent nitrogen atom numbers (shown in Scheme 1c–f, named as TM@N 3 C 1 ‐GR, TM@N 2 C 2 ‐GR‐I, TM@N 2 C 2 ‐GR‐II and TM@N 1 C 3 ‐GR, hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the N x C y ‐GR structures above, the effect of TM doping on electric property was further investigated [1f,7] . As shown in Figure 3 and Figure S2–S9, the band gap of TM@N x C y ‐GR materials are smaller than the N x C y ‐GR materials, and most TM@N x C y ‐GR materials show spin property.…”
Section: Introductionmentioning
confidence: 99%